Monitoring Jadwal Kuliah pada iClass Melalui Notifikasi Bot Telegram - Bata, Emanuel Safirman (STIKOM Uyelindo Kupang, 2021)
iClass has been used at STIKOM Uyelindo Kupang in the 2020/2021 academic year. Because of its very young age, iClass certainly still has some shortcomings that must be corrected so that teaching and learning activities can run even better. During the period of use, there are several obstacles that are felt by students, namely when there is a change in the class schedule made by the lecturer in charge of the course, students do not get notification, causing students not to take part in lecture activities. This of course will affect the recap of the lecture attendance list because it will be considered absent without explanation. In accordance with the rules at STIKOM Uyelindo Kupang contained in the 2020 academic manual, if a student does not attend without a maximum of 20% information, the student will be declared a failure and must be reprogrammed. Based on these problems, Telegram's Instant Messaging (IM) information technology feature is needed which can help iClass to send instant messages (Instant Messaging) automatically to students via mobile devices. Instant Messaging (IM) Telegram is one of the IM applications that is widely used by people around the world. One of the advantages of IM Telegram is that there is a basis for using the Application Programming Interface (API) for the wider community. one of the advantages of Bots is the reliability to provide data to users which is not limited by time. The use of IM applications has increased dramatically from year to year, although the use of IM still cannot completely replace SMS, along with the increase in mobile device users, the demand for data also increases. Telegram application that can be downloaded for free on Google Playstore. Because it is not paid, Telegram application users also experience an increase.